Mini electric sander belt machine: design, development, and testing - Mohd Bakhit, Muhammad Bariq; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Machines are designed to make tasks easier. They come in various sizes and price ranges, but smaller ones are often expensive and difficult to find. This project aims to address this issue by creating an affordable and compact electric sander belt. The process begins with designing the machine using software called SOLIDWORKS. Following the design phase, fabrication involved using tools like drills, cutters, and grinders, with aluminium as the primary material. The objective is to develop a small electric sander belt that activates with a switch. It was suitable for grinding small items such as shaping knives or reshaping drill bits. This mini machine particularly useful for small-scale projects and accessible to a wide range of users due to its affordability.